Caracterização das propriedades leiteiras: um estudo na cadeia produtiva da bovinocultura de leite no município de Toledo - PR - Bieger, Arlei (2010)
This paper addresses the issue of the productive chain of dairy cattle in the city of Toledo - Pr, in the cutout that covers the production stage, trying to analyze the characteristics of productive units of milk. We also use as reference the basic framework that covers the agribusiness concept and agro-industrial production chains. From this theory we identify the chain of production of milk and then the general characteristics of dairy cattle in Brazil and in Paraná, directing the focus to the work environment, the cow milk production in municipal sphere. After making the survey, the study identifies particular issues in a sample of dairy farmers participating in a program of the Department of Agriculture and Supply of Toledo (Secretaria de Agropecuária e Abastecimento do Município de Toledo). In the research, issues pertaining to development of the activity in establishments with milk production involved in condominiums of artificial insemination program are covered. For data collection, questionnaires were applied in 85 interviews with producers, seeking to identify characteristics of the main factors involved in milk production. The results from the survey were analyzed according to the volume of production of raw materials, and these producers were stratified into three groups by ranges of production, namely, up to 50 liters / day (small), between 51 and 250 liters / day (medium-sized) and above 250 liters / day (large). Following this segmentation, we identified the following three groups: 15.29% of small producers; 61.18% of medium-sized producers, and 23.53% of large producers. Based on these classes, the analysis covering a range of items was started: the properties and structure, the labor employed; issues applied to the herd, the milking and milk storage, economic indicators, the production support; management activity; marketing of milk; dissemination of Instruction 51; satisfaction and intentions of the producer. It was identified that the performance of large producers is better than the others , and although these properties require more investment and attention, it is the group that gets the best results. The intermediate class is more representative in the segment, and these producers invest significantly, but do not achieve results in the same proportion. Small farmers are the least privileged regarding resources and information, they do not consider themselves as managers of the activity and bear the burden of this deficiency. We conclude that the volume of milk produced is the major factor that guides the efforts of the producers, generating diversified forms of management among their respective properties. Such reality provides diverse results, due to this plurality, manager of the raw material producer segment on the milk productive chain of the city of Toledo PR.